Dampak Kapasitas Aerobik dan Elevation Training Mask (ETM) Menggunakan Metode High Intensity Interval Training (HIIT) Terhadap Kemampuan Fisiologik pada Pemain Futsal Putri - Asep Sumpena; Dikdik Zafar Sidik (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
This study was aimed at investigating the effect of using an Elevation Training Mask (ETM) with the High Intensity Interval Training (HIIT) Training Method on physiological abilities based on aerobic capacity. This research was an experimental study with a 2x2 factorial design. This study used aerobic and anaerobic physical component test instruments. This study involved 20 female futsal players as participants. Data analysis used statistical calculations with the help of the SPSS application. The results of the study showed that there was no increase in the physiological abilities of female futsal players based on the use of ETM. It indicated that there was an increase in the physiological ability of female futsal players based on aerobic abilities and there was no interaction between the use of ETM and aerobic capacity in increasing the physiological abilities of female futsal players. This study also concluded that female futsal players with high aerobic capacity were more effective than female futsal players with low aerobic capacity using the HIIT training method, both with high aerobic capacity using ETM and not using ETM compared to low aerobic capacity using ETM or without ETM. Apart from that, there was no interaction found. The implication of the research result shows that, in physical training, the training method must be adjusted to the aerobic capacity of the player by paying more attention to the principles of the training and specificity. Besides that, it is necessary to carry out further research using ETM to see the effect in lung capacity, so that it would be more comprehensive.